OPTIMIZING COMMUNITY-BASED WASTE MANAGEMENT: A REVIEW OF THE LITERATURE - Ramadha Yanti Parinduri; Cut Sah Kha Mei Zsazsa; Muhammad Yusup (JOURNAL OF COMMUNITY DEDICATION, 2023)
Increased waste production is one of the critical environmental problems worldwide. Optimizing waste management, especially community-based waste management, is considered an efficient solution in addressing this problem. This research uses a literature review approach, where data and information are collected from various sources including scientific journals, articles, research reports, and government documents relevant to community- based waste management. The results show that community involvement and active participation in waste management, environmental awareness education, and incentives are key factors in the success of community-based waste management. In addition, the role of the government is crucial in providing support in the form of favorable regulations, adequate infrastructure, and facilitation of collaboration between the community, government, and private sector. This study also found that the integration of technology in the waste management system contributes to improving the efficiency and effectiveness of the process.